USE OF INFORMATION TECHNOLOGIES IN GEOMETRIC PREPARE OF FUTURE TEACHERS OF MATHEMATICS - Grigorieva, В.Б. (Journal of Information Technologies in Education (ITE), 2010)
In article are considered the questions of using of computer technologies, for example, the software "Analytical geometry", in process of teaching course of analytical geometry in the higher school.